Grassroot Women’s Perspective on Interreligious Issues: A Sociocultural Analysis - Dewantri, Puja Alviana; Jayanti, Candra Dvi; Babtista Lemuel Christandi, Yohanes; Fabou Putera Koraag, Johanes; Firosa Ahda, M. Naufal (Jurnal Dialog, 2023)
Due to the presence of migrants and three large mosques that serve as centers of religious activities, 6,183 housewives in Pogung Kidul, or 18.02%, begin to interact with the growing diversity. Given their significant roles in promoting an open and inclusive understanding of religion within their families and social circles, this study aims to analyze how grassroot women’s interactions and involvement influence their perspectives on interfaith relations. Employing purposive sampling followed by semi-structured interviews with six housewives from the three large mosques of Pogung Kidul, namely Pogung Raya Mosque, Pogung Dalangan Mosque, and Pogung Baru Mosque, this qualitative study intends to investigate the complex interaction between women’s understanding of interfaith relations and the variables that influence their perspectives. Personal life experiences and the interaction of religious teachings emerged as the two primary factors that shaped their understanding and behavior within the context of the social community. They then internalized religious and social ethics, resulting in performative behaviors and attitudes that demonstrate piety and symbolize the spirit of Islamic revivalism while fostering positive social relations in an interreligious setting.